2021
DOI: 10.1177/15589250211025257
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial and ultraviolet protective neodymium-doped TiO2 film coated on polypropylene nonwoven fabric via a sputtering method

Abstract: A neodymium-doped titanium dioxide film was coated on polypropylene nonwoven fabric via a magnetron sputtering method to prepare multifunctional textiles with antibacterial and ultraviolet protective properties. The antibacterial property of the single-layer titanium dioxide film coated sample was better than that of the single-layer neodymium film coated sample. And that of the three-layer film coated samples was better than that of the double-layer film coated samples, which the latter also was superior to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…Ag/TiO 2 bilayer thin films Silver demonstrates outstanding electrical and optical properties, whereas TiO 2 exhibits a high photocatalytic activity and good chemical stability in addition to being environmentally friendly. The use of these materials to create functional fabrics has been the subject of numerous studies [13][14][15][16]18,[45][46][47][48][49]. Additionally, materials can be coated with these two substances to impart a structural colour.…”
Section: Colouring By Coating Bilayer Thin Filmsmentioning
confidence: 99%
“…Ag/TiO 2 bilayer thin films Silver demonstrates outstanding electrical and optical properties, whereas TiO 2 exhibits a high photocatalytic activity and good chemical stability in addition to being environmentally friendly. The use of these materials to create functional fabrics has been the subject of numerous studies [13][14][15][16]18,[45][46][47][48][49]. Additionally, materials can be coated with these two substances to impart a structural colour.…”
Section: Colouring By Coating Bilayer Thin Filmsmentioning
confidence: 99%
“…TiO 2 was said to have a synergistic impact on Cu [50]. Also, the neodymium-doped TiO2 film coated on polypropylene non-woven fabric via a sputtering method showed antibacterial and ultraviolet protective properties [60].…”
Section: Magnetron Sputtering (Ms) In Medical Textile Functionalizationmentioning
confidence: 99%
“…Infectious pathogens such as drug-resistant bacteria and viruses, including SARS-CoV-2, comprise serious public safety concerns worldwide and can significantly disrupt global commerce and human health. The development of safeguards against these biological threats is imperative; however, the sporadic nature of breakout events and the threat of new diseases that arise from novel microorganisms complicate the development of protective technologies. One important mode of transmission for these pathogens is through contaminated clothing and textiles as it has been shown that pathogens can survive on cloth for several days, increasing the likelihood of spreading disease. In light of this challenge, the biocidal treatment of cloth materials represents a promising strategy to decrease microbial contamination and reduce the spread of infection. , …”
Section: Introductionmentioning
confidence: 99%